Expression of Plasma Coagulase among Pathogenic Candida Species - Rodrigues, Acácio Gonçalves (American Society for Microbiology, 2003)
Candida coagulase production was assessed by the classical tube test. All Candida krusei strains were coagulase negative, but most C. albicans and C. tropicalis strains can produce coagulase. Some strains agglutinated the Pastorex Staph-Plus reagent, probably because of antigen similarities to coagulase produced by Staphylococcus aureus that may cause mistakes in clinical laboratories.